Wealth of Non Timber Forest Products and their Trade in Jammu and Kashmir - Gangoo, S. A.; Islam, M. A.; Mushtaq, Tahir (Indian Forester, 2017)
Globally NTFP / NWFP are defined as "forest products consisting of goods of biological origin other than wood, derived from forest, other wood land and trees outside forests". The Non Timber Forest Products (NTFPs) of Jammu and Kashmir are generally collected by the State Forest Department through lease to contractors. The state harbours a large variety of miscellaneous NTFP species that are collected by its people for self-use or petty sale to generate a part of their annual income. The dependence of local people on the NTFP resources reflects the significant impact of NTFPs on the local economy of the people of J&K. Studies conducted under sub project of Networking Project on NTFP funded by ICFRE Dehradun investigated the level of livelihood dependency on various NTFPs in J&K. The livelihood dependency on wicker handicraft has been studied in district Pulwama. Dependence on Punica granatum in livelihood of the people of district Ramban reveals that the anardana has a major share amounting to 48.78% in the net income of every household in the study area. Survey conducted in the markets of J&K revealed that different species are being sold in two different markets. This trade has been recorded from 2011 to 2015. NTFPs have a tremendous potential to involve local collectors for establishing micro-, small- and medium enterprises.